FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI MASYARAKAT DALAM BUDIDAYA BUAH NAGA DI NAGARI KETAPING KECAMATAN BATANG ANAI. - Aulia, Afdi Rahman; Dasrizal, Dasrizal; Yuherman, Yuherman (STKIP PGRI Sumbar, 2013)
The purpose of this research to find out information, analyza, and investigation about data factor-factor the influentially motivation people in cultivation At Nagari Kataping Kecamatan Batang Anai. This research will use correlation descriptive. The population of this study all 52 kk. farmer the cultivation dragon fruit at Nagari Kataping Kecamatan Batang Anai. Base on the analyza of simple regression, multiple, and correlation, so can be also conclude as follow : (1) have a influence the income factor on the people motivation in cultivation dragon fruit, the strong include influence ( r=0,699) and contribution to be given big enough (48,9%).(2) Have a influence the demand factor on the people motivation in cultivation dragon fruit, the strong include influence ( r=0,705) and contribution to be given big enough (49,7%).(3) Have a influence the income factor on the people motivation in cultivation dragon fruit, the strong include influence ( r=0,545) and contribution to be given big enough (29,8%).(4) Have a influence the income factor, demand factory, dan capital factory in a together on the people motivation in cultivation dragon fruit at Nagari Kataping Kecamatan Batang Anai, the strong include influence ( r=0,747) and contribution to be given big enough (55,8%).